A lithium silicomolybdate material and its preparation method and application

By adopting the new lithium silicon molybdate material, the problem of difficult improvement in the charge and discharge rate and capacity of existing lithium-ion battery materials has been solved, and the high performance of lithium-ion batteries has been achieved and there are wide application prospects.

CN118039890BActive Publication Date: 2025-02-14SHENZHEN XINYUANBANG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410075486.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-18
Publication Date
2025-02-14
Estimated Expiration
2044-01-18

AI Technical Summary

Technical Problem

Existing lithium-ion battery materials have limitations in improving battery performance, especially in terms of charge and discharge rate and capacity, which are difficult to significantly improve.

Method used

A new type of lithium silicon molybdate material is adopted, with a structure of Li4-2xSi1-xMoxO4, 0

Benefits of technology

The lithium silicon molybdate material exhibits excellent electrochemical properties in lithium-ion batteries, including high cycle capacity retention and good Coulomb efficiency, with potential application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118039890B_ABST
    Figure CN118039890B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium silicomolybdate material and a preparation method and application thereof. The structure of the lithium silicomolybdate material of the present invention is Li 4‑2x Si 1‑x Mo x O4, where 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery materials, and particularly relates to a lithium silicomolybdate material, a preparation method thereof, and an application thereof. Background Art

[0002] In recent years, with the development of new energy vehicles, lithium-ion batteries have been widely used due to their advantages such as high voltage, high energy density, long cycle life, low self-discharge, and no pollution. The positive electrode material, negative electrode material, battery separator, and electrolyte in a lithium-ion battery are the most important components of the lithium-ion battery, and their cost accounts for about 80% of the lithium-ion battery. How to improve the quality of lithium-ion batteries, such as properties such as charge and discharge rates and capacitance, is an important issue for the continued development of lithium-ion batteries. In the prior art, the battery performance is mostly improved by treating the positive and negative electrode materials, electrolyte, and separator; molybdate compounds are considered to be used as lithium-ion battery materials to improve the battery performance due to their good physical and chemical properties. Summary of the Invention

[0003] The present invention provides a novel lithium silicomolybdate material and a preparation method thereof, which have a wide range of application scenarios in lithium-ion batteries.

[0004] The present invention adopts the following technical solutions:

[0005] On the one hand, the present invention provides a lithium silicomolybdate material, and the structure of the lithium silicomolybdate material is Li 4-2x Si 1- x Mo x O4, where 0 < x ≤ 0.5; the crystal structure space group of the lithium silicomolybdate material is Pnma (No. 62).

[0006] Further, the lithium silicomolybdate material includes at least one of Li 3.8 Si 0.9 Mo 0.1 O4, Li 3.6 Si 0.8 Mo 0.2 O4, Li 3.4 Si 0.7 Mo 0.3 O4, Li 3.2 Si 0.6 Mo 0.4 O4, Li3Si 0.5 Mo 0.5 O4.

[0007] Further, the lithium silicomolybdate material is prepared by mixing a lithium precursor, a silicon precursor, and a molybdenum precursor;

[0008] The lithium precursor is selected from at least one of Li2CO3, LiOH·H2O, and Li2C2O4;

[0009] The silicon precursor is selected from at least one of SiO2, silane, and organosilicon;

[0010] The molybdenum precursor is selected from at least one of MoO3, ammonium molybdate and organic molybdenum.

[0011] Furthermore, the particle size of the lithium silicomolybdate material is 5 nm to 20 μm.

[0012] On the other hand, the present invention also provides a method for preparing the above-mentioned lithium silicomolybdate material, comprising the following steps:

[0013] (1) According to the structure of lithium molybdenum silicosilicate material, a lithium precursor, a silicon precursor and a molybdenum precursor are weighed, mixed and then ball-milled;

[0014] (2) The ball milled product is calcined at 250-350° C. for 1-10 h, then heated to 650-750° C. for 1-10 h, with a heating rate of 2-10° C. / min, and cooled to room temperature after calcination to obtain lithium molybdenum silicate material.

[0015] In another aspect, the present invention provides the use of the above-mentioned lithium silicomolybdate material or the lithium silicomolybdate material prepared by the above-mentioned preparation method in a lithium ion battery.

[0016] Furthermore, the lithium silicomolybdate material is used as a solid electrolyte material in a lithium-ion battery.

[0017] Furthermore, the lithium silicomolybdate material is used as a surface coating material of a negative electrode material or a negative electrode plate in a lithium-ion battery.

[0018] The lithium silicomolybdate material of the present invention is a new type of compound material containing silicon, molybdenum and lithium elements at the same time, and its crystal structure space group is Pnma (No.62). Different from traditional silicon-molybdenum materials and silicon-lithium materials, it exhibits excellent electrochemical properties. When it is used as a negative electrode material or a solid electrolyte material for lithium-ion batteries, the battery has excellent electrochemical properties such as cycle capacity retention rate and coulomb efficiency. The lithium silicomolybdate material of the present invention has potential application prospects in battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 is the XRD pattern of the lithium molybdenum silicic acid material prepared in Example 1;

[0021] Figure 2 is the XRD pattern of the lithium molybdenum silicic acid material prepared in Example 2;

[0022] Figure 3 is the XRD pattern of the lithium molybdenum silicic acid material prepared in Example 3;

[0023] Figure 4 is the XRD pattern of the lithium molybdenum silicic acid material prepared in Example 4;

[0024] Figure 5 is the XRD pattern of the lithium molybdenum silicic acid material obtained in Example 5;

[0025] Figure 6 is the XRD pattern of the lithium molybdenum silicic acid material obtained in Example 6;

[0026] Figure 7 is the XRD pattern of the lithium molybdenum silicic acid material obtained in Example 7;

[0027] Figure 8 is the XRD pattern of the lithium molybdenum silicic acid material obtained in Example 8;

[0028] Fig. 9 This is the XRD pattern of the lithium molybdenum silicic acid material prepared in Comparative Example 1;

[0029] Fig.10 This is the XRD pattern of the lithium molybdenum silicic acid material prepared in Comparative Example 2;

[0030] Fig.11 This is the XRD pattern of the lithium molybdenum silicic acid material prepared in Comparative Example 3;

[0031] Fig.12 This is the XRD pattern of the lithium molybdenum silicic acid material prepared in Comparative Example 4;

[0032] Fig.13 It is a first cycle charge and discharge curve diagram of a lithium ion battery using the lithium molybdenum silicic acid material prepared in Example 1 as the negative electrode material at 0.5C. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0034] The present invention provides a lithium silicomolybdate material, wherein the structure of the lithium silicomolybdate material is Li4-2x Si 1-x Mo x O4, where 0 < x ≤ 0.5; the crystal structure space group of the lithium silicomolybdate material is Pnma (No. 62).

[0035] The lithium silicomolybdate material of the present invention is a novel compound material containing silicon, molybdenum and lithium elements simultaneously, having a novel crystal structure different from traditional silicon molybdenum materials and silicon lithium materials, showing excellent electrochemical properties and having potential application prospects in battery systems.

[0036] Specifically, the lithium silicomolybdate material includes Li 3.8 Si 0.9 Mo 0.1 O4, Li 3.6 Si 0.8 Mo 0.2 O4, Li 3.4 Si 0.7 Mo 0.3 O4, Li 3.2 Si 0.6 Mo 0.4 O4, Li3Si 0.5 Mo 0.5 O4 or at least one of them.

[0037] In some embodiments of the present invention, the lithium silicomolybdate material is prepared by mixing a lithium precursor, a silicon precursor and a molybdenum precursor;

[0038] The lithium precursor is selected from at least one of Li2CO3, LiOH·H2O, Li2C2O4;

[0039] The silicon precursor is selected from at least one of SiO2, silane, organosilicon; more specifically, the silicon precursor is selected from at least one of SiO2, methylsilane, methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl chlorophenyl silicone oil, methyl ethoxy silicone oil, methyl trifluoropropyl silicone oil, methyl vinyl silicone oil, methyl hydroxy silicone oil, vinyl silane, amino silane, methacryloxy silane, methyl trichlorosilane, dimethyldichlorosilane, phenyl trichlorosilane, diphenyldichlorosilane.

[0040] The molybdenum precursor is selected from at least one of MoO3, ammonium molybdate, organomolybdenum; more specifically, the molybdenum precursor is selected from at least one of MoO3, ammonium molybdate, dialkyldithiocarbamate molybdenum, molybdenum amine complex, naphthenic acid molybdenum, alkyl salicylic acid molybdenum.

[0041] In some preferred embodiments of the present invention, the lithium precursor is selected from Li2CO3, the silicon precursor is selected from SiO2, and the molybdenum precursor is selected from MoO3.

[0042] In some embodiments of the present invention, the particle size of the lithium silicomolybdate material is 5 nm to 20 μm.

[0043] On the other hand, the present invention also provides a method for preparing the above-mentioned lithium silicomolybdate material, comprising the following steps:

[0044] (1) According to the structure of lithium molybdenum silicosilicate material, a lithium precursor, a silicon precursor and a molybdenum precursor are weighed, mixed and then ball-milled;

[0045] (2) The ball milled product is calcined at 250-350° C. for 1-10 h, then heated to 650-750° C. for 1-10 h, with a heating rate of 2-10° C. / min, and cooled to room temperature after calcination to obtain lithium molybdenum silicate material.

[0046] In some embodiments of the present invention, the ball milling treatment time is 10 to 120 minutes; after the ball milling, the process also includes drying and grinding the ball milled slurry to ensure the fineness of the raw materials.

[0047] In another aspect, the present invention provides the use of the above-mentioned lithium silicomolybdate material or the lithium silicomolybdate material prepared by the above-mentioned preparation method in a lithium ion battery.

[0048] In some embodiments of the present invention, the lithium silicomolybdate material is used as a solid electrolyte material in a lithium ion battery.

[0049] In some embodiments of the present invention, the lithium silicomolybdate material is used as a surface coating material of a negative electrode material or a negative electrode plate in a lithium-ion battery.

[0050] The following will describe in conjunction with specific embodiments.

[0051] 1. Lithium Silicate Molybdate Material

[0052] Example 1

[0053] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0054] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0055] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0056] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 750° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0057] Example 2

[0058] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0059] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0060] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5 O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 are weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads are added and mixed in a planetary ball mill, and the slurry is dried and ground after the ball milling;

[0061] (2) The ground product was calcined in a muffle furnace. The calcination procedure was first calcined at 350° C. for 1 h, then heated to 700° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0062] Example 3

[0063] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0064] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0065] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5O4 structure, lithium precursor LiOH·H2O, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 6:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0066] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 680° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0067] Example 4

[0068] This embodiment provides a lithium silicomolybdate material, the structure of which is Li 3.2 Si 0.6 Mo 0.4 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0069] Li 3.2 Si 0.6 Mo 0.4 The preparation of O4 comprises the following steps:

[0070] (1) According to lithium molybdenum silicic acid material Li 3.2 Si 0.6 Mo 0.4 O4 structure, lithium precursor Li2CO3, silicon precursor methyl silicone oil and molybdenum precursor alkyl salicylate molybdenum are weighed in a molar ratio of 16:3:4, isopropanol and zirconium beads are added, mixed in a planetary ball mill, and ball milled;

[0071] (2) The ball-milled product was calcined in a muffle furnace at 300° C. for 5 h, then heated to 650° C. for 1 h, with an overall heating rate of 2° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0072] Example 5

[0073] This embodiment provides a lithium silicomolybdate material, the structure of which is Li 3.4 Si 0.7 Mo 0.3 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0074] Li 3.4 Si 0.7 Mo 0.3 The preparation of O4 comprises the following steps:

[0075] (1) According to lithium molybdenum silicic acid material Li 3.4 Si 0.7Mo 0.3 O4 structure, lithium precursor Li2C2O4, silicon precursor methylsilane and molybdenum precursor ammonium molybdate (NH4)2MoO4 were weighed in a molar ratio of 17:7:3, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0076] (2) The ball-milled product was calcined in a muffle furnace at 250° C. for 10 h, then heated to 720° C. for 8 h, with an overall heating rate of 10° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0077] Example 6

[0078] This embodiment provides a lithium silicomolybdate material, the structure of which is Li 3.6 Si 0.8 Mo 0.2 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0079] Li 3.6 Si 0.8 Mo 0.2 The preparation of O4 comprises the following steps:

[0080] (1) According to lithium molybdenum silicic acid material Li 3.6 Si 0.8 Mo 0.2 O4 structure, lithium precursor LiOH·H2O, silicon precursor methylsilane and molybdenum precursor dialkyldithiocarbamate molybdenum were weighed in a molar ratio of 18:4:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0081] (2) The ball-milled product was calcined in a muffle furnace at 280° C. for 8 h, then heated to 700° C. for 6 h, with an overall heating rate of 4° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0082] Example 7

[0083] This embodiment provides a lithium silicomolybdate material, the structure of which is Li 3.8 Si 0.9 Mo 0.1 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0084] Li 3.8 Si 0.9 Mo 0.1 The preparation of O4 comprises the following steps:

[0085] (1) According to lithium molybdenum silicic acid material Li 3.8 Si 0.9 Mo 0.1 O4 structure, lithium precursor Li2C2O4, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 19:9:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0086] (2) The ball-milled product was calcined in a muffle furnace at 320° C. for 3 h, then heated to 660° C. for 10 h, with an overall heating rate of 8° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0087] Example 8

[0088] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4; the crystal structure space group of the lithium molybdenum silicic acid material is Pnma (No.62).

[0089] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0090] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5 O4 structure, lithium precursor Li2SO4, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0091] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 750° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0092] Comparative Example 1

[0093] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4.

[0094] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0095] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0096] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 770° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0097] Comparative Example 2

[0098] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4.

[0099] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0100] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5 O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0101] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 620° C. for 3 h, with an overall heating rate of 5° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0102] Comparative Example 3

[0103] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4.

[0104] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0105] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5 O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0106] (2) The ball-milled product is calcined in a muffle furnace at 750° C. for 4 h and then naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0107] Comparative Example 4

[0108] This embodiment provides a lithium silicomolybdate material, the structure of which is Li3Si 0.5 Mo 0.5 O4.

[0109] Li3Si 0.5 Mo 0.5 The preparation of O4 comprises the following steps:

[0110] (1) According to the lithium silicomolybdate material Li3Si 0.5 Mo 0.5 O4 structure, lithium precursor Li2CO3, silicon precursor SiO2 and molybdenum precursor MoO3 were weighed in a molar ratio of 3:1:1, isopropanol and zirconium beads were added, mixed in a planetary ball mill, and ball milled;

[0111] (2) The ball-milled product was calcined in a muffle furnace at 350° C. for 1 h, then heated to 750° C. for 3 h, with an overall heating rate of 12° C. / min. After calcination, the product was naturally cooled to room temperature to obtain lithium molybdenum silicate material.

[0112] The lithium silicomolybdate materials prepared in Examples 1-8 and Comparative Examples 1-4 were subjected to XRD testing. The results are as follows: Figure 1-12 shown.

[0113] XRD test method: D8 Advance ECO X-ray diffractometer was used for XRD test, with Ka line of copper target as ray source, voltage of 40 kV, current of 30 mA, 2θ range of test of 10-80°, step length of 0.02° / step, step speed of 0.3 sec / step.

[0114] Depend on Figure 1-12 It can be seen that the XRD graph of the lithium silicomolybdate material prepared in each embodiment has obvious characteristic peaks corresponding to the Pnma crystal structure and no obvious impurities, indicating that the corresponding lithium silicomolybdate material can be prepared by this method; the XRD graph of the lithium silicomolybdate material prepared in each comparative example has obvious impurity peaks.

[0115] 2. Lithium Silicate Molybdate Material as Negative Electrode Material for Lithium-ion Battery

[0116] The lithium silicomolybdate materials prepared in Examples 1-8 and Comparative Examples 1-4 were respectively ground into powders, and the negative electrode active material (i.e., lithium silicomolybdate material), acetylene black and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) was added, mixed to form a slurry, evenly coated on a copper foil, and vacuum dried at 80°C for 9h, and a nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode.

[0117] The negative electrode sheet, separator, and lithium foil were stacked and injected with electrolyte to form a sandwich structure button battery. Then, constant current charge and discharge tests were performed, and the results were valid data for the first 100 cycles. The test current density was 50mA / g, and the voltage range was 0.01~3V. The results are shown in Table 1.

[0118] The lithium silicomolybdate material of Example 1 was used as the negative electrode material in the lithium ion battery and the first cycle charge and discharge test was carried out at 0.5C. The results are as follows: Fig.13 shown.

[0119] Table 1

[0120]

[0121]

[0122] It can be seen from Table 1 that the lithium-ion batteries using the lithium silicomolybdate material as the negative electrode prepared in each embodiment have a high discharge specific capacity and good cycle stability. The discharge specific capacity and cycle stability in the comparative example are significantly deteriorated due to the presence of impurities. Specifically, as can be seen from the test results of Example 1 and Comparative Examples 1 to 4, the lithium silicomolybdate material prepared by the roasting process of the present invention is used as the negative electrode material of the lithium-ion battery, and the battery has better coulombic efficiency and cycle capacity retention rate; as can be seen from the test results of Example 1 and Example 8, by selecting a specific lithium precursor raw material, the prepared lithium silicomolybdate material has better battery performance when used as the negative electrode material. Fig.13 As shown, the lithium silicomolybdate material of Example 1 is used as the negative electrode material in the lithium ion battery. During the stable cycle process, the discharge capacity of the negative electrode material is 520 mAh / g and the charging capacity is 500 mAh / g.

[0123] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A lithium silicomolybdate material, characterized in that: The structure of the lithium silicomolybdate material is Li 4-2x Si 1-x Mo x O4, where 0 < x ≤ 0.5; the crystal structure space group of the lithium silicomolybdate material is Pnma (No. 62).

2. The lithium silicomolybdate material according to claim 1, characterized in that: The lithium silicomolybdate material includes Li 3.8 Si 0.9 Mo 0.1 O4、Li 3.6 Si 0.8 Mo 0.2 O4、Li 3.4 Si 0.7 Mo 0.3 O4、Li 3.2 Si 0.6 Mo 0.4 O4、Li3Si 0.5 Mo 0.5 At least one of O4.

3. The lithium silicomolybdate material according to claim 1, characterized in that: The lithium silicomolybdate material is prepared by mixing a lithium precursor, a silicon precursor and a molybdenum precursor; The lithium precursor is selected from at least one of Li2CO3, LiOH·H2O, and Li2C2O4; The silicon precursor is selected from at least one of SiO2, silane, and organosilicon; The molybdenum precursor is selected from at least one of MoO3, ammonium molybdate and organic molybdenum.

4. The lithium silicomolybdate material according to claim 1, characterized in that: The particle size of the lithium silicomolybdate material is 5nm-20μm.

5. The method for preparing the lithium silicomolybdate material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) According to the structure of lithium molybdenum silicosilicate material, a lithium precursor, a silicon precursor and a molybdenum precursor are weighed, mixed and then ball-milled; (2) The ball milled product is calcined at 250-350° C. for 1-10 h, then heated to 650-750° C. for 1-10 h, with a heating rate of 2-10° C. / min, and cooled to room temperature after calcination to obtain lithium molybdenum silicate material.

6. Use of the lithium silicomolybdate material according to any one of claims 1 to 4 or the lithium silicomolybdate material prepared by the preparation method according to claim 5 in lithium ion batteries.

7. The use according to claim 6, characterized in that: The lithium silicomolybdate material is used as a solid electrolyte material in a lithium ion battery.

8. The use according to claim 6, characterized in that: The lithium silicomolybdate material is used as a surface coating material of a negative electrode material or a negative electrode plate in a lithium ion battery.

Citation Information

Patent Citations

  • Lithium molybdate cathode material for lithium ion battery and preparation method thereof

    CN104241642A